EVALUASI PROGRAM PEMBERDAYAAN MASYARAKAT MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 (STUDI KASUS PROGRAM DESA MAJU INHIL JAYA DI DESA DANAU PULAI INDAH DAN DESA KARYA TANI KECAMATAN KEMPAS (KABUPATEN INDRAGIRI HILIR) - Muhammad April; Muammar Alkadafi (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2020)
The Integrated Village of Inhil Jaya (DMIJ) Plus Program, is the flagship program of the Government of Indragiri Hilir Regency. This research is to find out the implementation of the Integrated Maju Inhil Jaya Plus Village (DMIJ) program, the impact of the implementation and the constraints of the Integrated DMIJ Plus program in Danau Pulai Indah Village and Karya Tani Village. The research method used a qualitative research approach, with evaluative research types by case studies. Sources of data obtained through observation, documents, and in-depth interviews (indepth interview), with key informants; Village Heads, Village Officials, BPD, LKMD, community leaders and community group representatives. The results of the study, showed that the implementation of the Maju Inhil Jaya Village program in Danau Pulai Indah Village and Karya Tani Village covered 4 (four) fields of activities that were not fully implemented, the program implementation was still conservative-involutive. The integrated DMIJ Plus program has a positive impact on the field of village governance, the field of village development, and the field of village community development can also be said to be good. while the field of village community empowerment, the desired results have not been good or less than the maximum. The impact of the DMIJ program has not been fully felt by the community, the contribution of the program is still minimal in the field of community empowerment. The constraints are the still limited quality of the human resources of the program implementers, and the program target communities.